Food Delivery Service New Trends and its Impact on Customer Satisfaction in Pangasinan - Rricky Tim S. Sison (Southeast Asian Journal of Science and Technology, 2023)
The study have utilized a descriptive quantitative design with the aim to assess customer satisfaction with specific online food delivery services in order to enhance standard operating procedures of food delivery services in Lingayen, Pangasinan. It was conducted from the standpoint of the participants' satisfaction with the chosen food aggregators' food delivery services. The sample size of 215 customers was computed based on the projected population using the Rao soft sample size calculator. The SERVQUAL Model questionnaire, a multi-item scale designed was used to gauge the degree of customer satisfaction in service, that served as a research instrument. The study have used an adapted questionnaire that was modified to fit the objectives of the study. The results revealed that Generation Z and single respondents have a more favorable opinion of and higher level of satisfaction with the effectiveness of food delivery services in Lingayen, Pangasinan. This suggests that the younger generation will likely make up the majority of the clients using the online food delivery services. It shows that customization to using online platforms and mobile apps for various purposes, including ordering food has significance to online food service delivery and level of satisfaction towards it. Their familiarity and comfort with technology make them more likely to embrace online food service delivery and have higher satisfaction with the convenience it offers. Interestingly, this study found that food quality factors related to food delivery services were not proven significant. This research may provide several theoretical advances to the body of knowledge already written about online food delivery services.